Draft Third Five Year Plan 1961-66 (Volume VIII) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1961)
The Second Plan envisaged only a modest programme of publicity. The need has now been felt for providing more effective machinery for publicity of the Plan so that people's support and cooperation towards the implementation of the Plan may be forth coming in increasing measure. The Plan has to be carried into every home in the language and symbols of the people and expressed in terms of their common needs and problems.
Andaman and Nicobar Administration